Pemberian Edukasi terkait Anemia Menggunakan Media Leaflet dan PowerPoint terhadap Pengetahuan Remaja di Desa Kalimas, Kecamatan Besuki, Kabupaten Situbondo - Dinda Arum Sari (Universitas Airlangga, 2024)
Background: Anemia can be considered a significant health issue among Indonesian teenagers, with a relatively high incidence rate of 32%. Within the age range of 15-24 years, the incidence rate of anemia among teenage girls reaches 27.2%, while among teenage boys it is 20.3%. One of the regions in Indonesia with a relatively high incidence rate of anemia is Situbondo Regency. It is known that 49% of pregnant women and teenage girls have sufficient and insufficient knowledge regarding anemia and iron supplement consumption. Preventing and managing anemia in adolescents can be achieved by increasing their knowledge and understanding of anemia and its effects. Providing education to adolescents can be done through lecture and discussion methods. Objectives: Increase the knowledge of Kalimas Village adolescents regarding anemia and encourage them to develop a supportive environment to improve adherence to regular and sustainable consumption of blood supplement tablets. Methods: This community service was implemented using a quasi-experimental one-group pretest-posttest design. The subjects of the education implementation consisted of 10 adolescents from the age range of 12 to 20. Data on adolescent knowledge related to anemia was obtained through pretest and posttest questionnaires. The education on anemia was delivered through lecture and discussion methods using leaflets and PowerPoint as media. Results: The statistical analysis conducted using the Paired Sample T-Test indicates that the average knowledge score of adolescents before and after receiving education increased. The p-value of 0.000, which is significantly smaller than 0.05, suggests a significant difference in the level of knowledge among adolescents before and after receiving education. Conclusions: The provision of education through lectures and discussions, utilizing leaflets and PowerPoint media related to anemia, can effectively enhance adolescents' knowledge. It is hoped that similar activities can be conducted regularly and sustainably, accompanied by a monitoring scheme for blood tablet consumption as a form of effort to reduce the incidence of anemia and accelerate the reduction of stunting rates in Indonesia.